(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Predictors for severe COVID-19 infection have not been well defined especially in Bangladeshi patients. This study was aimed to investigate the association between clinical and laboratory parameters and the mortality from COVID-19 infections in patients admitted in two Government Hospitals in Chattogram, Bangladesh. Materials and methods: This prospective observational study included 178 confirmed COVID-19 (By reverse transcription polymerase chain reaction test) patients aged ³ 18 years, admitted in Chittagong Medical College Hospital and Chittagong General Hospital, Chattogram, Bangladesh. Socio-demographic and clinical characteristics on admission were recorded. Patients were categorized as survivors (Improved and discharge, n=148) and deceased (Expired in hospital, n=30). Analyses were performed using SPSS version 23.0. Results: Median age for deceased cases and for survived cases were 57.5 and 55 years respectively with male predominance in both groups. Majority of the patients were from urban area (65.2%) and from upper lower (42.7%) socio-economic class. In univariate analysis mortality was associated with being from upper or middle socio-eco nomic class, presence of hypertension, diabetes, pre-existing renal disease (p=0.004) and having difficulty breathing at admission. Moreover, compared to the survivors, deceased cases were associated with lower levels oxygen saturation, lymphocytes, elevated levels of leukocytes, neutrophil tolymphocyte ratio, D-dimer and ferritin at admission. Conclusions: Factors associated with mortality in this study might improve our understanding of COVID19 progression and provide baseline data to compile or improve the prediction models for the estimation of COVID-19 prognosis in Bangladesh. JCMCTA 2020 ; 31 (2) : 19-24